Long-term use of benzodiazepine among depressed patients / Tan Chea Loon - Tan, Chea Loon (2012)

(untitled)
Long-term benzodiazepine use in depression is not recommended by the treatment guidelines. Nevertheless, its prevalence is still remaining high. In order to prevent long-term use, it is important to know which determinant factors are associated with it. This may create awareness among the clinicians and take further measures regarding this issue. The purpose of this study was to determine the prevalence of long-term benzodiazepines use among depressed patients in the specialty mental health setting and identify the socio-demographic, clinical and psychosocial factors that associated with the long-term use. This was a retrospective cross-sectional study involving 65 outpatients with major depressive disorder in specialty mental health setting. We investigate the socio-demographic, clinical and psychosocial factors which associated with long-term benzodiazepine use. The prevalence of long-term benzodiazepines use among depressed patient was 70.2%. Long-term use of benzodiazepines were significantly associated with more severe of depressive symptoms (p=0.038), more severe anxiety symptoms (p=0.004), poor functioning level (p=0.047), poor social support (p=0.015) and poor religiosity (p=0.010). There was significant association between long-term use of benzodiazepines among depressed patient with severity of depressive and anxiety symptoms, level of functioning, social support and religiosity. This associations found point to possibilities to reduce long-term benzodiazepine use, for example if patient still having residual depressive and anxiety symptom, the medication and treatment plan should be further optimized.